2020
DOI: 10.1097/aln.0000000000003206
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic Intrathecal Morphine and Prevention of Post–Dural Puncture Headache

Abstract: Background Prophylactic epidural morphine administration after unintentional dural puncture with a large-bore needle has been shown to decrease the incidence of post–dural puncture headache. The authors hypothesized that prophylactic administration of intrathecal morphine would decrease the incidence of post–dural puncture headache and/or need for epidural blood patch after unintentional dural puncture. Methods Parturients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Different intrathecal catheter medications have been evaluated to determine their ability to influence the rate of post‐dural puncture headache. Recent interest in the use of intrathecal morphine to prevent post‐dural puncture headache includes a small randomised controlled trial comparing 27 women who received intrathecal morphine 150 µg through the intrathecal catheter after delivery to a control group of 34 women who received 0.6–1 ml of intrathecal normal saline [33]. There was no difference in the incidence of post‐dural puncture headache or the need for epidural blood patch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different intrathecal catheter medications have been evaluated to determine their ability to influence the rate of post‐dural puncture headache. Recent interest in the use of intrathecal morphine to prevent post‐dural puncture headache includes a small randomised controlled trial comparing 27 women who received intrathecal morphine 150 µg through the intrathecal catheter after delivery to a control group of 34 women who received 0.6–1 ml of intrathecal normal saline [33]. There was no difference in the incidence of post‐dural puncture headache or the need for epidural blood patch.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported greater vasopressor use in the intrathecal catheter group than in the re‐sited epidural group (33/129 (25.6%) vs. 2/52 (3.8%), p < 0.001, OR (95%CI) 8.59 (1.98–37.28) [18]; the cause of this difference was presumed to be the effect of the lidocaine/epinephrine test dose in the intrathecal vs. epidural space. In a study using intrathecal morphine to diminish post‐dural puncture headache, respiratory rate and sedation level were assessed clinically by the nursing staff every hour for 12 h initially postpartum, followed by every 2 h for the next 12 h [33]. In a study of intrathecal catheter side‐effects by Izquierdo et al., women with intrathecal catheters received a post‐procedure assessment at 24, 48 and 72 h [18].…”
Section: Resultsmentioning
confidence: 99%
“…Other reasons include the regular disinfection measures and change of the external infusion tube in every visit with an interval of 2 weeks, care transitions in the long‐term ITT, and the careful prevention measures in daily life (Qin et al., 2020 ). The most frequent surgical complication was post‐dural puncture headache in both groups, which suggests no significant difference in the risk of pericatheter CSF leakage between the two ITT systems (Adler & Lotz, 2017 ; Peralta et al., 2020 ). The incidences of intrathecal opioid‐induced adverse events are much the same in the two groups, and the most frequent adverse events were nausea/vomiting and urinary retention, which is in accordance with other studies (J. H. Kim et al., 2013 ; Mastenbroek et al., 2017 ; Qin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…A recent randomized double -blind controlled trial evaluated prophylactic intrathecal morphine injection for prevention of PDPH. The authors found that a single prophylactic morphine injection does not decrease the incidence or severity of PDPH [15]. Brinser et al [14] reviewed 80 cases where 38 women were given neuraxial morphine and 42 were not.…”
Section: Risk Factorsmentioning
confidence: 99%